To solve the system of equations y = 3x + 6 and y = -13x - 4, we can set the right sides of the equations equal to each other:
3x + 6 = -13x - 4
Next, let's add 13x to both sides and subtract 6 from both sides to isolate the variable x:
3x + 13x + 6 - 6 = -13x + 13x - 4 - 6
16x = -10
Now, divide both sides by 16 to solve for x:
(16x) / 16 = (-10) / 16
x = -10/16
Simplifying the fraction gives:
x = -5/8
Now that we have the value of x, we can substitute it back into one of the original equations to solve for y. Let's use the first equation y = 3x + 6:
y = 3(-5/8) + 6
y = -15/8 + 48/8
y = 33/8
Therefore, the solution to the system of equations is x = -5/8 and y = 33/8.
solve following system of equations
y = 3x + 6
y = -13x - 4
1 answer